Evaluasi Atas Kebijakan Peningkatan Rasio Siswa SMK:SMA Ditelaah dari Kesiapan Sarana dan Prasarana - Barliana, Mukhammad Syaom; Maknun, Djohar; Herman, Kunthi (INVOTEC, 2010)
The policy to increase ratio of the number of students between vocational high school (SMK) and senior high school (SMA) being 70:30 in 2014, needs to be supported by policy to improve both quality and quantity of teachers, infrastructures, diversification of skills, and absorption of graduates in job market. Using quantitative descriptive approach, this research reveals that availability of infrastructures in all vocational high schools in Bandung city at present, and how the projection in the future. The result of this research shows that at present situation, when the comparison of the number of students SMK:SMA is 50:50, it proves that generally SMK with state status just fulfill exactly about 75% equipment and quality in accordance with infrastructure national standards.